Metaproteomic Insights Into the Microbial Community in Pozol - Rizo, Jocelin; Guillén, Daniel; Díaz-Ruiz, Gloria; Wacher, Carmen; Encarnación, Sergio; Sánchez, Sergio; Rodríguez-Sanoja, Romina (Frontiers in Nutrition, 2021)
Pozol is an acidic, refreshing, and nonalcoholic traditional Mayan beverage made with nixtamalized corn dough that is fermented spontaneously. The extensive analysis of the microbiology, biochemistry and metaproteomics of pozol allowed the construction of a comprehensive image of the fermentation system. The main changes in both the substrate and the microbiota occurred in the first 9 hours of fermentation. The increase in microorganisms correlated with the drop in pH and with the decrease in the contents of carbohydrates, lipids, and nitrogen, which shows that this stage has the highest metabolic activity. Bacteria were mainly represented by lactic acid bacteria, and among them, the genus Streptococcus was overwhelmingly the most abundant. Yeasts were present in all the analyzed samples, while filamentous fungi increased up to 48 h. The metaproteomic approach allowed us to identify several previously unknown enzyme complexes in the system. Additionally, enzymes for hydrolysis of starch, hemicellulose and cellulose were found, indicating that all these substrates can be used as a carbon source by the microbiota. Finally, enzymes related to the production of essential intermediates involved in the synthesis of organic acids, acetoin, butanediol, fatty acids and amino acids important for the generation of compounds that contribute to the organoleptic characteristics of pozol, were found.